Toleransi Beragama sebagai Upaya Mewujudkan Moderasi Beragama pada Generasi Z di Kota Medan: Kajian Literatur - Khairani Soraya; Khairul Fahri; Dia Marisah; Fitri Helmainun; M Ilyas (Jurnal Keluarga Sehat Sejahtera, 2026)
This study discusses the level of tolerance and the implementation of religious moderation among Generation Z in Medan City. The aim of the research is to examine the understanding, attitudes, challenges, and strategies for strengthening religious tolerance among young people in a diverse society. The research uses a qualitative approach with a library research method based on scientific journals, books, official reports, and previous studies. The findings show that Generation Z has a relatively good understanding of tolerance and tends to be socially open. However, their attitudes are still influenced by social media, peer groups, and limited interfaith dialogue spaces. The main challenges include social media algorithms, politicization of religion, and education approaches that are not yet fully inclusive. Therefore, strengthening religious moderation should be carried out through education, digital media utilization, and interfaith dialogue spaces.